Removal of Total Petroleum Hydrocarbons from Contaminated Soil with Used Lubricating Oil by Surfactant : Triton X-100, and Cow Manure Amendments - Suttichareon, Saowalak; Wibuloutai, Jindawan; Prathumchai , Nuchnapa; Suttichareon, Supachai (Burapha Science Journal, 2026)
This study aims to evaluates the effects of surfactant: Triton X-100, and cow manure compost on the removal of total petroleum hydrocarbons (TPHs) from contaminated soil with used lubricating oil (ULO). Soils spiked with about 700 gkg-1 (7% w/w) of ULO were individually amended with 0.3% w/v, 0.5% w/v and 0.7% w/v of Triton X-100. One kilograms of soil amended with 0.5% w/v of Triton X-100 was mixed with caw manure compost in the ratio of 1:0.3 w/w, 1:0.5w/w and 1:0.7w/w soil mixture: caw manure compost. The results showed that the highest total petroleum hydrocarbons reduction efficiency of 64.65±1.25% was achieved in the 0.5% w/v oil-contaminated remediated with of Triton X-100, the highest TPH-removal of 72.50 ±1.48% could also be achieved in the ratio of 1:0.5 w/w oil contamination condition with of cow manure amendments for a 28-day experiment period. The results indicated that cow manure could significantly enhance TPH-removal (from 64% to 72%). The findings highlight the prospect of cow manure as a proper nutrient for enhanced remediation of hydrocarbon-contaminated soils.